(untitled) (Bangladesh Journal of Agricultural Research, 2023)
A questionnaire survey was conducted with 600 growers in six potato growing areas of Bangladesh viz. Munshiganj, Barisal-Patuakhali, Dinajpur-Thakurgaon, Joypurhat, Jamalpur-Sherpur and Jashore-Chuadanga to collect a detailed information about potato storage at home and in cold storages along with their disposal pattern. The survey revealed that 55.2% growers store their potatoes in the cold storages. Due to the proximity of cold storages (within 1-10 km from the home/field) majority potato growers of Munshiganj (82%), Dinajpur-Thakurgaon (81%) and Joypurhat (70%) stored in cold storages. On the other hand, majority growers of Barisal-Patuakhali (88%) and Jamalpur-Sherpur (73%) could not store due to lack or long distance of cold storages. The growers disposed up their cold stored potatoes mainly by selling to local paikers at cold storage gate or by using as seed. While considering all areas, 56.0 % farmers stored potatoes at home in the studied areas. Majority farmers in Dinajpur-Thakurgaon (91%), Joypurhat (98%) and Jamalpur-Sherpur (65.0%) areas stored potato at home. Farmers of these areas stored upto 150 days at home because of cultivation of local varieties. Regarding disposal of home stored potatoes, the growers mainly sold to local paikers or at local market or used for own family consumption or by other means. Bangladesh J. Agril. Res. 47(1): 23-38, March 2022